Do Bulls and Bears Move Across Borders? International Transmission of Stock Returns and Volatility - Lin, Wen-Ling; Engle, Robert F.; Ito, Takatoshi (Review of Financial Studies, 1994)
This article investigates empirically how returns and volatilities of stock indices are correlated between the Tokyo and New York markets. Using intradaily data that define daytime and overnight returns for both markets, we find that Tokyo (New York) daytime returns are correlated with New York (Tokyo) overnight returns. We interpret this result as evidence that information revealed during the trading hours of one market has a global impact on the returns of the other market. In order to extract the global factor from the daytime returns of one market, we propose and estimate a signal extraction model with GARCH processes.